Good Practices to Reduce Noise Levels in the Neonatal Intensive Care Unit - Alberto Alves Carvalhais, Carlos (2019)
Indoor environmental conditions in neonatal intensive care units, such noise levels above the recommended, may induce some risks, not only for preterm infants’ development, but also for health care staff. The aim of this work is to summarize some good practices guidelines that can be followed by health care staff in a daily basis, which are intended to promote noise reduction in neonatal intensive care units. It is expected some initial resistance to the implementation of some recommendations, but evidence shows that in general, with training, health care staff should recognize the need of changes.